Manajemen Arsip sebagai Bagian Hidup Organisasi: Studi Kasus di Dinas Perpustakaan dan Kearsipan Kota Magelang - Nora Saiva Jannana; Ria Susi Nur Fadhilah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to describe the management of two types of archive, dynamic and static, in the Library and Archives Office of Magelang, Central Java. This is a case study with a qualitative approach. The data were collected through interviews, observation, and documentation, and were analyzed using the interactive model techniques by Miles and Huberman. The research found that: (1) management of the records consists of dynamic and static archives; (2) the archival storage is carried out independently and used classification system of problems; (3) the management of active dynamic archives consists of receiving of records, indexing, appointing, dispositioning, follow-up, and filing; (4) the management of inactive dynamic archives consist of selection, description, grouping, determination of schedule for archival retention, structuring, pengkamperisasian, and filing; (5) the management of static archives consist of planning, source identification, archival information maneuvering and definitive numbering, arrangement for storage (compiling inventory, labeling, validating inventory lists and binding inventory lists).